Tilapia gift production performance and quality cultured under different culture systems - Farah Farhanim Mohd Zin (2017)
The growth performance, feed utilization, sensory evaluation, proximate and fatty acid composition of Genetically Improved Farmed Tilapia (GIFT) reared in different culture systems were examined in 126 days of feeding trials. Throughout the feeding trial, fish were fed commercial tilapia feed twice a day at 3 % of their body weight. In the present study, there was a higher range of temperature, pH, salinity and nitrite of cage culture system compared to the tank culture system. However, only ammonium content of water was significantly affected by the culture systems. It was found that significantly higher viscerosomatic and hepatosomatic indices, weight gain, daily growth rate, specific growth rate, gross yield and better feed conversion ratio were yielded in GIFT cultured in cage (9.16 %, 2.50 %, 267.06 g, 2.67 g fish⁻1 day-1, 3.90 % day-1, 24.43 g fish-1 day-1 and 1.06, respectively) than in tank (5.38 %, 1.26 %, 172.55 g, 1.50 g fish-1 day-1, 2.07 % day-1, 18.84 g fish-1 day-1 and 1.41, respectively). In contrast, GIFT cultured in tank showed significantly higher survival rate (100.00±0.00 %) and ash content (1.45±0.66 %) than GIFT cultured in cage (94.00±1.15 %; 1.05±0.56 %, respectively). Length-weight relationship showed both GIFT reared in either tank or cage culture systems have strong positive relationship. GIFT reared in cage showed a heavier and bigger size (b=3.07) compared to tank culture system (b=2.58). There were significant different (P<0.05) in mean total weight of GIFT between both culture systems. In the present study the values of relative condition factor (K) of GIFT from tank and cage culture systems; showed ideal growth (0.8605 and 1.2285, respectively). The daily feed consumption varied considerably for both culture systems, but there was an upward trend in consumption at the beginning of trials and the maximum feeding rates for the whole system in the tank and cage were approximately 2,500 g/day and 2,300 g/day, respectively. Apart from that, higher positive scores obtained in sensory evaluation test indicated that the acceptance of consumers toward GIFT fillets cultured in both systems. Nevertheless, panels claimed to like or most prefer fillets of GIFT cultured in tank more than GIFT cultured in cage to be chosen as a food product. A higher contents of 20:5n-3 (0.29±0.09 %) and 22:6n-3 (14.59±0.23 %) of GIFT fillets cultured in tank culture systems proposed that GIFT cultured in tank culture systems richer of EPA and DHA omega-3 which widely recognized to be beneficial for human health and nutrition. In our study, suggested that a higher proportions of UFAs of GIFT fillets cultured in tank culture system than those cultured in cage were mainly influenced by significantly different size of fish and maturity factor in the two culture systems during harvest. Growth performance of GIFT in this study shows various possibilities of manipulation of culture systems in aquaculture industry. It can be concluded that both systems have their own advantages and disadvantages in terms of growth, survival and fillet quality of GIFT. Therefore, findings from the present study indicated that both culture systems are feasible to be practiced in Malaysia depending on the farm‟s objective and availability of culture facility.